Administrative efficiency and its relationship to crisis management among the deans of Colleges of Baghdad governorates from the point of view of department heads - Saleh, Mohamed Ahmed (Al-Adab Journal, 2022)
Higher education in the modern era faces many challenges represented by the explosion of knowledge, and this requires revitalizing the role of university administration to be able to carry out its new duties, as it is no longer appropriate to manage universities in the same ways they were managed in the past, as educational institutions suffer from an administrative legacy burdened with challenges on the Despite the efforts made in their attempts to develop themselves, and universities are witnessing serious attempts to develop all their systems, and colleges are the basic unit of the university, and accordingly, the efficiency of administrative work is largely related to the role of its members and the effective administrative work they provide to manage the crises facing their institutions. Which necessitates saying that the deans of faculties depend their success on their administrative competence, as well as on providing the appropriate climate to manage the crises they face. The importance of the research lies in describing the university as a leader of development and progress. It also calls for the existence of an effective administration in administrative efficiency that works to achieve its goals for which it was established and to confront crises that obstruct its work, as the importance of crisis management becomes clear through following the scientific method in how to contain the crisis and reduce of which. research aims: The current research aims to identify: The level of administrative competence among the deans of the faculties of Baghdad universities from the point of view of the heads of departments. The level of crisis management among the deans of the faculties of the Baghdad governorate from the point of view of the heads of departments. The correlative relationship between administrative efficiency and crisis management among the deans of faculties of universities in Baghdad governorate from the point of view of department heads. The research community included the heads of departments in the faculties of the universities of the province of Baghdad, which amounted to (419) department heads for all faculties. Specialized experts in the field of management, measurement and evaluation, as well as through another indicator, which is the validity of construction. As for the stability; It was verified by two methods, the first being the test and re-testing, and the second method is the method of analysis of variance using the Facronbach equation, and the most important statistical methods used are (Pearson correlation coefficient, Facronbach equation, one-sample t-test).